COLLIER'S ENCYCLOPEDIA - Halsey, William D. (dirección) (CROWELL-COLLIER, 1964)
CONTENIDO: V. 1 A-AMELAND. -- V. 2 AMEN-ARTILLERY. -- V. 3 ART NOUVEAU-BEETLE. -- V. 4 BEEVILLE-BURMESE. -- V. 5 BURNAP-CHARM. -- V. 6 CHARNY-COLONIE. -- V. 7 COLONNA-DECATUR. -- V. 8 DECCAN-ELECTRON. -- V. 9 ELECTRON GUN-FISCHER. --V. 10 FISCUS-GERMANICUS. -- V. 11 GERMANIUM-HEATH HEN. -- V. 12 HEATING-INFANTRY. -- V. 13 INFINITY-KATMAI. -- V. 14 KATMANDU-LONGHI. -- V. 15 LONGINUS-META. -- V. 16 METAL-MUSIAL. -- V. 17 MUSIC-NUMAZU. -- V. 18 NUMBER-PHRYGIA. -- V. 19 PHYFE-RENI. -- V. 20 RENNER-SIBELIUS. -- V. 21 SIBENIK-SYLACAUGA. -- V. 22 SYLT-URUGUAY. -- V. 23 USA-ZWORYKIN. -- V. 24 BIBLIOGRAPHY-INDEX